Latent Autoimmune Diabetes in Adults (LADA): From Immunopathogenesis to Immunotherapy - Hu, Jingyi; Zhang, Rong; Zou, Hailan; Xie, Lingxiang; Zhou, Zhiguang; Xiao, Yang (Frontiers in Endocrinology, 2022)
Latent autoimmune diabetes in adults (LADA) is a type of diabetes characterized by slow autoimmune damage of pancreatic β cells without insulin treatment in the early clinical stage. There are differences between LADA and classical type 1 diabetes (T1D) and type 2 diabetes (T2D) in genetic background, autoimmune response, rate of islet function decline, clinical metabolic characteristics and so on. The disease progression and drug response of patients with LADA are closely related to the level of islet autoimmunity, thus exploring the pathogenesis of LADA is of great significance for prevention and treatment. Previous studies reported that adaptive immunity and innate immunity play a critical role in the etiology of LADA. Recent studies have shown that the intestinal microbiota which impacts host immunity hugely, participates in the pathogenesis of LADA. In addition, the progression of autoimmune pancreatic β cell destruction in LADA is slower than in classical T1D, providing a wider window of opportunities for intervention. Therefore, therapies including antidiabetic drugs with immune-regulation effect and immunomodulators could contribute to promising interventions for LADA. We also shed light on potential interventions targeting the gut microbiota and gut-associated immunity, may be envisaged to halt or delay the process of autoimmunity in LADA.